Tanggapan Warga Belajar terhadap Penggunaan Metode Pembelajaran oleh Instruktur pada Program Diklat Perhotelan di SPNF SKB Kota Payakumbuh - Misbah Hayati; Wirdatul Aini; Irmawita Irmawita (Universitas Negeri Padang, 2018)
This research is based on the hospitality training process in SPNF-SKB Payakumbuh that good. This condition is suspected because it has something to do with the use of methods used by instructors. This study aims to describe the use of instructional methods by instructors according to studying citizens in hospitality training which include: (1) use of lecture methods, (2) use of demonstration methods, (3) use of training methods. This research includes quantitative descriptive research that describes the data as it is. The population is thirty-five people and the sample of twenty-three people is determined based on sampling technique that is stratified random sampling technique. The data collection tool uses a questionnaire. Data analysis using percentage formula. From the result of the research, it can be seen that the responses of learners to the use of instructional methods of instructors can be good (1) the use of lecture method in hospitality training is categorized well, (2) use of demonstration method in hospitality training is categorized as good, (3) use of training method in hospitality training categorized good.